Performance characteristics between TDx®FLx and TBA™-25FR for the therapeutic drug monitoring of methotrexate. Issue 1 (December 2016) - Kaneko, Tetsuya; Fujioka, Takashi; Suzuki, Yosuke; Sato, Yuhki; Itoh, Hiroki
Abstract Background High-dose methotrexate (HDMTX) is used in the treatment of certain malignancies, including leptomeningeal metastases, systemic non-Hodgkin lymphoma, acute lymphoblastic leukemia, and osteosarcoma. High circulating levels of methotrexate can cause severe myelosuppression. The present study aimed to examine the differences in plasma MTX concentrations measured by two immunoassay systems currently available in the Japanese market, a TDX /FLX analyzer and a TBA-25FR analyzer. Methods A total of 69 plasma samples from 16 patients were assayed by a fluorescence polarization immunoassay technique using a TDx/FLx analyzer (Abbott Diagnostics, Chicago, Illinois, U.S.A.) and a homogeneous enzyme immunoassay technique using a TBA-25FR analyzer (Toshiba Medical Systems, Tokyo, Japan). Results Assay results were very consistent between the two systems, with good correlation 24 h after the start of treatment (TBA-25FR = 1.06・TDX /FLX, −1.31, r  = 0.99), 48 h after the start of treatment (TBA-25FR = 1.00・TDX /FLX, +0.027, r  > 0.99), and 72 h after the start of treatment (TBA-25FR = 1.09・TDX /FLX, +0.011, r  > 0.99). Conclusions The calibration curve spanned one order of magnitude with a linear working range from the lowest to the highest standard. The standard deviations show the excellent reproducibility of repeated measurements at each standard level for both immunoassay systems. However, when using the TBA-25FR, it is necessary to perform measurements in the low-concentration range with care.